Channels of science communication and sources of scientific knowledge in Poland - Podgórniak-Krzykacz, Aldona (Science Communication in Poland. Participation. Dialogue. Trust, 2021)
Public interest in science requires the involvement of numerous channels and information sources through which scientific knowledge can be communicated to a wide audience. Traditional and modern digital solutions are used in deficit, discussion and participatory models of science communication. Television, the press, and popular science books are still the main sources of scientific knowledge for the public, and the level of credibility of these knowledge sources is high due to the involvement of scientists who create this knowledge. The Internet is another channel used for science communication, and its importance in popularising science has definitely increased. Sources of scientific knowledge for the public include websites, the scientific blogosphere, and, increasingly often, social media. Popularisers of science mainly use Facebook, YouTube and Twitter. The use of these media makes it easier to reach a wider audience – especially younger audiences – with scientific information, but also to exchange views and encourage public discussions. Modern science centres, scientific events, and citizen science offer the most engaging way for the public to interact with science. They provide opportunities for direct contact with science and scientists, and they stimulate curiosity and inspire people to learn about phenomena and discover the world on their own. At the same time, citizen participation contributes to increased confidence in science.